EKSISTENSI PENDIDIKAN TOLERANSI BERAGAMA BERBASIS LITERASI BUDAYA DAN KEWARGAAN DALAM ERA MEDIA 4.0 - Latif Pertiwi; Nanda Veruna Enun Kharisma (Tatar Pasundan : Jurnal Diklat Keagamaan, 2022)
This study aims to describe the existence of cultural and civic-based religious tolerance education at SDN 04 Sipkanyin in the media moderation 4.0 era. This research uses a qualitative approach, case study model. The research data collection used observation, interviews, and documentation. The results showed that SDN 04 Sipkanyin has displayed the existence of religious tolerance through learning, school culture, and student self-development by utilizing existing modern technology. Through learning, lesson plan, implementation, assessment, and evaluation are succesfully observed. The academic culture is sensed through installing school’s vision and mission, and discipline. Religious cooperation and guidance are manisfested through democratic culture. Students' self-development is executed through routine extracurricular activities, literacy, religious harmony movies, morning apples, and Monday ceremonies. Spontaneous activities are in form of reprimands, advice, and praise. Exemplary is given through the provision of examples by teachers. Conditioning is by providing infrastructures. Keywords: Religious Tolerance Education; Cultural Literacy and Citizenship; Media Era 4.0